1986
DOI: 10.1177/104438948606700803
|View full text |Cite
|
Sign up to set email alerts
|

Main Street Revisited: Social Work Practice in Rural Areas

Abstract: The unique aspects of rural social work practice are discussed, with emphasis on the relationship between rural values and primary social work methods and skills. Suggestions for meeting the professional development needs of rural social workers are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Our review of the literature revealed very few articles that specifically address rural couple and family issues (e.g., Anderson, 1976;Bagarozzi, 1982;Boyer, 1987;Brownlee, 1994;Jurich & Russell, 1987;Markowski & Cain, 1983;Piercy, Hovestadt, Fenell, Franklin, & McKeon, 1982;Whittington, 1985;Williams, 1975). In contrast, the fields of psychology and social work have given considerable focus to rural practice issues (e.g., Childs & Melton, 1983;Denton, York, & Moran, 1988;Flax et al, 1978;Ginsberg, 1998;Gumpert & Saltman, 1998;Keller & Murray, 1982;Reschly & Connolly, 1990;Wagenfeld et al, 1994;Waltman, 1986;Weitz, 1992). The purpose of this article is to review the available literature regarding rural couple and family counseling, in conjunction with the findings of research in closely related fields.…”
mentioning
confidence: 99%
“…Our review of the literature revealed very few articles that specifically address rural couple and family issues (e.g., Anderson, 1976;Bagarozzi, 1982;Boyer, 1987;Brownlee, 1994;Jurich & Russell, 1987;Markowski & Cain, 1983;Piercy, Hovestadt, Fenell, Franklin, & McKeon, 1982;Whittington, 1985;Williams, 1975). In contrast, the fields of psychology and social work have given considerable focus to rural practice issues (e.g., Childs & Melton, 1983;Denton, York, & Moran, 1988;Flax et al, 1978;Ginsberg, 1998;Gumpert & Saltman, 1998;Keller & Murray, 1982;Reschly & Connolly, 1990;Wagenfeld et al, 1994;Waltman, 1986;Weitz, 1992). The purpose of this article is to review the available literature regarding rural couple and family counseling, in conjunction with the findings of research in closely related fields.…”
mentioning
confidence: 99%
“…It is also important to consider those areas in which rural and urban women did not differ. Previous literature has stressed the importance of selfreliance (Weinert & Long, 1987;Waltman, 1986) and preference for informal informational networks among rural residents (Dillman & Beck, 1988). Although not an exact measure of self-reliance, the Hope Scale used in this study showed no differences in personal agency and perceived problem solving.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to economic and social characteristics, health and well-being of rural women may be affected by psychosocial processes characteristic of rural environments (Dillman & Beck, 1988;Waltman, 1986). For example, people in rural environments have traditionally favored acquiring information and accepting change by relying on informal social networks, such as kin and neighbors, versus formal ones, such as health professionals (Weinert & Long, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Even today, gays and lesbians lack access to many social programs available to their heterosexual counterparts (Barranti & Cohen, 2000;Smith & Mancoske, 1997). Vulnerable populations are likely to confront unique problems in rural communities because many residents in rural communities are wary of diversity (Waltman, 1986).…”
Section: Diversity In Rural Communitiesmentioning
confidence: 99%
“…Community context has been viewed for more than two decades as the central organizing frame for rural social work practice (Ginsberg, 2000;Martinez-Brawley, 1980a, 1985Martinez-Brawley & Carlton, 1982;Sundet & Mermelstein, 1983;Waltman, 1986). In fact, "fitting into" the community has been emphasized in guidance offered to social workers planning to practice in rural communities (Ginsberg, 2000;Schmidt, 2000).…”
Section: Introductionmentioning
confidence: 99%